Financial Health Analyze of Building Construction Sub-Sector BUMN Companies on the Indonesian Stock Exchange Period 2020 – 2022 - Putri, Kartika Malika; Sam, Iskandar; Tiswiyanti, Wiwik (Asian Journal of Management Analytics, 2024)
This research aims to analyze the financial health of state-owned companies in the building construction sub-sector on the Indonesia Stock Exchange in 2020-2022 using 8 ratios, namely ROE, ROI, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, Total Asset Turnover, and TMS to TA . The type of data used in this research is secondary data. This type of research is descriptive research with a quantitative approach. The results of the research show that PT Wijaya Karya received a BB rating in the "LESS HEALTHY" category from 2020-2022, then PT Pembangunan Perumahan in 2020 received a B rating and increased to a BB rating in the "LESS HEALTHY" category during 2021-2022, then PT Adhi Karya in 2020-2021 received a B rating and increased in 2022 to BB with the "LESS HEALTHY" category, then PT Waskita Karya in 2020 obtained a CCC rating with the "NOT HEALTHY" category then in 2021-2022 it increased to a B rating with “LESS HEALTHY” category.